Improving Scale-Up Procedures for Solids Friction and Minimum Transport Boundary for Fluidized Dense-Phase Pneumatic Conveying Systems - Setia, Gautam (My University, 2016)
This thesis presents results of an ongoing investigation into developing a validated modeling procedure of important design criteria, such as solids friction factor (for the accurate prediction of pressure drop) and minimum transport condition for the fluidized dense-phase pneumatic conveying of powders. In spite of having the potential of being energy economic mode of pneumatic transport, reliable design of fluidized dense-phase pneumatic conveying systems is still a difficult task due to the highly turbulent and complex nature of the flow of fine powders under high concentrations, where it is difficult to model the particle-wall-air interactions. Major efforts in this thesis have gone to develop pneumatic conveying test facility at the Laboratory for Particle and Bulk Solids Technologies, Thapar University, India for the fluidized dense-phase flow of fine powders having different pipeline configurations, such as 43 mm I.D. × 24 m long, 54 mm I.D. × 24 m long and 69 mm I.D. × 24 m long and 54 mm I.D. × 70 m long pipes. Indian fly ash was conveyed in fluidized dense-phase. Additional tests (under scale-up condition) were performed by conveying of cement and a different sample of fly ash through the 65 mm I.D × 254 m long and 80/100 mm I.D × 407 m long test rigs of Fujian Longking Co., China. Existing data of other researcher (from the laboratory of University of Wollongong, Australia), where ESP dust and fly ash were conveyed through 69 mm I.D. × 168 m long, 105 mm I.D. ×168 m long and 69 mm I.D. × 554 m long pipelines, were also used for comprehensive scale-up validation of the developed models. A new technique of modeling solids friction factor has been developed using new dimensionless numbers, volumetric loading ratio and dimensionless velocity (the ratio of particle free settling velocity to superficial conveying air velocity) by replacing the solids loading ratio and Froude numbers, respectively, present in the existing models. The volumetric loading ratio term incorporates the effect of product volume occupancy inside the pipeline, which was considered in this study to be a better representation of the flow conditions compared to the mass flow rate ratio of solids to air (solids loading ratio). The dimensionless velocity term is aimed at addressing the flow condition (transition from non-suspension to suspension flow). Models have been developed using the straight-pipe conveying data of three types of fly ash, cement and ESP dust (median particle diameter: 7 to 30 μm; particle density: 1950 to 3637 kg/m3; loose-poured bulk density: 610 to 1080 kg/m3). The models were evaluated for their accuracy and stability under significant scale-up conditions by comparing the predicted versus experimental pneumatic conveying characteristics obtained from longer and larger sized pipelines. Results have shown that the new model has considerably improved pressure drop predictions (up to 66.2%) compared to the prediction capability of the existing model, especially in the dense-phase region. In another approach, a two-layer based model has been developed by separately considering the solids friction contributions of the non-suspension (dense) bed of powders flowing along the bottom of pipe and the suspension (dilute-phase flow) of particles occurring on top of the non-suspension layer. Volumetric loading ratio and dimensionless velocity have been used to represent the non-suspension dune flow layer. A solids impact and friction term has been employed to represent the dilute-phase flow due their established reliability. The developed models for solids friction were validated for their scale-up accuracy by using them to predict the pressure drops in above mentioned larger and longer pipelines and by comparing the experimental versus predicted pneumatic conveying characteristics. The two-layer model provided further considerable improvement in prediction indicating that the model is able to adequately address the dense- to dilute-phase transition criteria. For the reliable design of fluidized dense-phase pneumatic conveying systems, it is of paramount importance to accurately estimate blockage conditions or the minimum transport boundary. Based on the test results of 22 different powders conveyed through 38 pipelines, a unified model for the minimum transport boundary has been developed that represents gas Froude number as a function of solids loading ratio and particle Froude number. The model has been validated by predicting the minimum transport boundary for 3 different products, conveyed through 6 different pipelines. Various other existing models have been validated for the same products and pipelines. Comparisons between experimental blockage boundary and predicted results have shown that the newly developed model provides more accurate and stable predictions compared to the other existing models. The model incorporates both pipe diameter effect and some important physical properties of the particles. The model is believed to be useful in predicting minimum conveying velocities for various fine powders that are fluidizable to ensure optimum operating point for industrial pneumatic conveying systems.
PhD thesis
Keywords: pneumatic conveying; fluidized; dense phase; modelling